2020
DOI: 10.2147/ppa.s233472
|View full text |Cite
|
Sign up to set email alerts
|

<p>Outpatients’ Satisfaction in the Context of 10 Years of Health-Care Reform: A Cross-Sectional Study of Tertiary Hospitals in Shiyan, China</p>

Abstract: These authors contributed equally to this workPurpose: This study aimed to evaluate outpatient satisfaction in tertiary hospitals in Shiyan, China, to predict which items had highest priorities for outpatient satisfaction, and to identify population groups on which the medical institutions should focus. Patients and Methods: A cross-sectional survey was conducted at three tertiary hospitals in Shiyan city of China, from March to June 2018. An 18-item outpatient satisfaction questionnaire was applied. We conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…Previous studies had shown that patients were more dissatisfied with medical expenses in this dimension. [2][3][4]17 This lower satisfaction could be explained by the patients' high expectations for the medical services of tertiary hospitals and the gap between ideal and reality. Thomas's research indicated that patient experience may not directly relate to the quality of medicinal care, but patient satisfaction is closely related to high-quality treatment procedures.…”
Section: The Service Efficiency Dimension Had the Highest Score While The Hospital Environment Dimension Was The Oppositementioning
confidence: 99%
“…Previous studies had shown that patients were more dissatisfied with medical expenses in this dimension. [2][3][4]17 This lower satisfaction could be explained by the patients' high expectations for the medical services of tertiary hospitals and the gap between ideal and reality. Thomas's research indicated that patient experience may not directly relate to the quality of medicinal care, but patient satisfaction is closely related to high-quality treatment procedures.…”
Section: The Service Efficiency Dimension Had the Highest Score While The Hospital Environment Dimension Was The Oppositementioning
confidence: 99%
“…Particularly, the hospital pharmacists play an increasingly important role in improving medication adherence, the role of which includes assessing medication adherence, identifying predisposing factors, providing consultations, and recommending targeted medication adherence strategies. The patients' medication adherence is inevitably correlated with the performance of pharmacists, 5,6 while it may also be dominated by their own social and psychological factors. Some pharmacists fail to fulfill the responsibilities expected by patients, resulting in patients' dissatisfaction with the attitude and behavior of pharmacists in pharmaceutical service, which may exert an adverse effect on the medication adherence of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Kualitas pelayanan kesehatan sebagai investasi dalam peningkatan angka kunjungan yang berhubungan positif dengan Indeks Kepuasan Masyarakat di fasilitas pelayanan kesehatan seperti Rumah Sakit (Liu et al, 2021;Ai et al, 2022). Tingkat kepuasan baik pada instalasi rawat jalan, rawat inap dan Unit Gawat Darurat (IGD) berperan penting dalam evaluasi kebijakan untuk meningkatkan kualitas dan pemanfaatan layanan kesehatan (Asamrew et al, 2020;Ke et al, 2020).…”
Section: Pendahuluanunclassified